Multi-targeted Antisense Oligonucleotide Delivery by a Framework Nucleic Acid for Inhibiting Biofilm Formation and Virulence - Zhang, Yuxin (Nanomicro Lett, 2020)
Biofilm formation is responsible for numerous chronic infections and represents a serious health challenge. Bacteria and the extracellular polysaccharides (EPS) cause biofilms to become adherent, toxic, resistant to antibiotics, and ultimately difficult to remove. Inhibition of EPS synthesis can prevent the formation of bacterial biofilms, reduce their robustness, and promote removal. Here, we have developed a framework nucleic acid delivery system with a tetrahedral configuration. It can easily access bacterial cells and functions by delivering antisense oligonucleotides that target specific genes. We designed antisense oligonucleotide sequences with multiple targets based on conserved regions of the VicK protein-binding site. Once delivered to bacterial cells, they significantly decreased EPS synthesis and biofilm thickness. Compared to existing approaches, this system is highly efficacious because it simultaneously reduces the expression of all targeted genes (gtfBCD, gbpB, ftf). We demonstrate a novel nucleic acid-based nanomaterial with multi-targeted inhibition that has great potential for the treatment of chronic infections caused by biofilms. [Image: see text]